Digitalisasi Penerimaan Siswa Baru: Integrasi Sistem Informasi Manajemen dalam SPMB MI Terpadu Ar Rifqi Tahun Ajaran 2026/2027 - Padli Abdul Jabar (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to analyze the integration of the Management Information System (MIS) in the New Student Admission System (SPMB) at Ar Rifqi Integrated Madrasah for the 2026/2027 Academic Year, as well as to examine the extent to which its implementation is in line with the principles of efficiency, transparency, and accountability. The main issue examined is whether the digitization of SPMB in the madrasah has reflected the optimal application of MIS according to the latest literature findings. The research uses a qualitative method with a case study approach, relying on SPMB document analysis as the main data source. The results show that MI Terpadu Ar Rifqi has adopted the basic elements of MIS through online registration, WhatsApp confirmation, and a segmented fee structure, but has not yet fully integrated automation features, data security, and real-time dashboards. Thus, the implementation of MIS is still semi-digital and is in a transitional stage between the relational values of Islamic education and the demands of modern digital governance. Keywords: Management Information System; Education Digitalization; New Student Admission. Keywords: Management Information System; Education Digitalization; New Student Abstrak Penelitian ini bertujuan untuk menganalisis integrasi Sistem Informasi Manajemen (SIM) dalam Sistem Penerimaan Murid Baru (SPMB) di MI Terpadu Ar Rifqi Tahun Ajaran 2026/2027, serta mengkaji sejauh mana implementasinya selaras dengan prinsip efisiensi, transparansi, dan akuntabilitas. Masalah utama yang dikaji adalah apakah digitalisasi SPMB di madrasah tersebut telah mencerminkan penerapan SIM yang optimal sesuai temuan literatur terkini. Penelitian menggunakan metode kualitatif dengan pendekatan studi kasus, mengandalkan analisis dokumen SPMB sebagai sumber data utama. Hasil menunjukkan bahwa MI Terpadu Ar Rifqi telah mengadopsi elemen-elemen dasar SIM melalui pendaftaran daring, konfirmasi WhatsApp, dan struktur biaya tersegmentasi, namun belum sepenuhnya mengintegrasikan fitur otomatisasi, keamanan data, dan dashboard real-time. Dengan demikian, implementasi SIM masih bersifat semi-digital dan berada pada tahap transisi antara nilai relasional pendidikan Islam dan tuntutan tata kelola digital modern. Kata kunci: Sistem Informasi Manajemen; Digitalisasi Pendidikan; Penerimaan Siswa Baru.